Ethno-racial inequalities on adverse birth and neonatal outcomes: a nationwide, retrospective cohort study of 21 million Brazilian newbornsResearch in context - Poliana Rebouças; Enny S. Paixão; Dandara Ramos; Julia Pescarini; Elzo Pereira Pinto-Junior; Ila R. Falcão; Maria Yury Ichihara; Samila Sena; Rafael Veiga; Rita Ribeiro; Laura C. Rodrigues; Maurício L. Barreto; et al. (Elsevier, 2024)
Summary: Background: Ethno-racial inequalities are critical determinants of health outcomes. We quantified ethnic-racial inequalities on adverse birth outcomes and early neonatal mortality in Brazil. Methods: We conducted a cohort study in Brazil using administrative linked data between 2012 and 2019. Estimated the attributable fractions for the entire population (PAF) and specific groups (AF), as the proportion of each adverse outcome that would have been avoided if all women had the same baseline conditions as White women, both unadjusted and adjusted for socioeconomics and maternal risk factors. AF was also calculated by comparing women from each maternal race/skin colour group in different groups of mothers' schooling, with White women with 8 or more years of education as the reference group and by year. Findings: 21,261,936 newborns were studied. If all women experienced the same rate as White women, 1.7% of preterm births, 7.2% of low birth weight (LBW), 10.8% of small for gestational age (SGA) and 11.8% of early neonatal deaths would have been prevented. Percentages preventable were higher among Indigenous (22.2% of preterm births, 17.9% of LBW, 20.5% of SGA and 19.6% of early neonatal deaths) and Black women (6% of preterm births, 21.4% of LBW, 22.8% of SGA births and 20.1% of early neonatal deaths). AF was higher in groups with fewer years of education among Indigenous, Black and Parda for all outcomes. AF increased over time, especially among Indigenous populations. Interpretation: A considerable portion of adverse birth outcomes and neonatal deaths could be avoided if ethnic-racial inequalities were non-existent in Brazil. Acting on the causes of these inequalities must be central in maternal and child health policies. Funding: Bill & Melinda Gates Foundation and Wellcome Trust.